2020
DOI: 10.26552/com.c.2020.2.3-14
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Functioning Efficiency of the Working Warehouse of the "UVK Ukraine" Company Transport and Logistics Center

Abstract: Competition in the field of logistics and individual transport services requires the constant analysis of logistics chains and their individual links. Given analysis enables implementation of new approaches to logistics companies and networks trade marketing in the offtake of certain types of goods. Industrial and commercial enterprises have to expand their trade and economic relations with other regions with the aim to provide the necessary sales volumes in the domestic market of regions and to go beyond it. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Logistics, as the name suggests, refers to the flow of materials from suppliers to consumers. It includes information, transportation, storage, material handling, and packaging [9,10]. Figure 1 illustrates the logistics process.…”
Section: Logistics System Optimization Methodsmentioning
confidence: 99%
“…Logistics, as the name suggests, refers to the flow of materials from suppliers to consumers. It includes information, transportation, storage, material handling, and packaging [9,10]. Figure 1 illustrates the logistics process.…”
Section: Logistics System Optimization Methodsmentioning
confidence: 99%
“…Thus, the research [1] deals with optimization of the warehouse operation using mathematical and statistical modeling. This made it possible to determine the warehouse operation optimal parameters and obtain a positive optimization effect expressed in a reduction of the total costs by 17.2 %, increase of the output flowrate by 34.6 % and average input flow intensity values of 10.3 %.…”
Section: Reference Reviewmentioning
confidence: 99%
“…Two papers explicitly share the results of an implementation phase of their model. Aulin et al (2020) were allowed eight days to record data for variable sensitivity analyses (e.g., on the number of workers engaged and product flow). Furthermore, the research at Renault reported by Serrano, Delorme, and Dolgui (2015) for cross-docking internal operation planning was followed up with an 8-week implementation of a simplified version of the developed solution method.…”
Section: General Overview Of Cross-docking Literaturementioning
confidence: 99%